Evaluation of the Thermo Scientific RapidFinder™ Salmonella Species, Typhimurium, and Enteritidis Multiplex PCR Kit. (23rd November 2019) - Scopes, Emma; Screen, Jessica; Evans, Katharine; Crabtree, David; Hughes, Annette; Kaupinen, Mikko; Flannery, Jonathan; Bird, Patrick; Benzinger, M Joseph; Agin, James; Goins, David; Chen, Yi; et al.
Abstract: The Thermo Scientific RapidFinder™ Salmonella Species, Typhimurium, and Enteritidis Multiplex PCR Kit (candidate method) is a real-time PCR assay for the detection and differentiation of Salmonella spp., and the serovars S. Typhimurium, and S. Enteritidis from poultry, pork, and environmental samples. The method was validated in comparison to the U.S. Department of Agriculture Food Safety and Inspection Service and the U.S. Food and Drug Administration reference methods. Thermo Fisher Scientific (Basingstoke, United Kingdom) tested all matrixes. In addition, two matrixes were analyzed independently by Q Laboratories, Inc. (Cincinnati, OH). Few statistically significant differences were found between the candidate and reference methods when analyzed by probability of detection. When differences were observed, these were in favor of the candidate method. All 200 inclusivity strains and none of the 45 exclusivity strains were detected, which demonstrated that the RapidFinder Salmonella Species, Typhimurium, and Enteritidis Multiplex PCR Kit was able to detect all the major groups of Salmonella, the less common subspecies of S. enterica, and the rarely encountered S. bongori . None of the exclusivity isolates analyzed were detected. Robustness testing demonstrated that the assay gave reliable performance, with specific method deviations outside the recommended parameters. Accelerated stability testing was conducted, validating the assay shelf life.